Measuring farm-level agrobiodiversity in Nariño, Colombia A large-scale assessment using agriculture census data - Zepeda, Adair; Alvarez, Jose A; Odjo, Sylvanus; Lopez-Ridaura, Santiago (CIMMYT, 2025)
Agrobiodiversity is an important source of food through direct consumption or trade; it also helps preserve local biodiversity and genetic resources within communities. However, its measurement implies important costs or operational considerations for large-scale sampling. In this study, the 2019 second-semester Agriculture Census of Colombia was used to estimate the Shannon-Weiner Index for diversity in the Nariño department in Colombia.